Lipolytic bacteria and the dynamics of flavor production in Indonesian tempeh - Naswandi Nur; Anja Meryandini; Maggy Thenawidjaja Suhartono; Antonius Suwanto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nur N, Meryandini A, Suhartono MT, Suwanto A. 2020 Lipolytic bacteria and the dynamics of flavor production in Indonesian Tempeh. Biodiversitas 21: 3818-3825. During the process of tempeh maturation, lipolytic bacteria become an integral part of tempeh and even have important roles in determining the quality of resulting tempeh. This study was conducted to examine correlation between lipolytic bacteria which were present in three tempeh samples i.e. CMG, EMP, RTI, and their roles in liberation of free fatty acid. Lipolytic bacteria were found in each tempeh sample which were approximately 0.1 % of total bacterial population. CMG harbored the highest lipolytic bacterial population at 1.04 × 106 cfu g-1 followed by EMP at 2.88 × 105 cfu g-1, and RTI at 1.72 × 104 cfu g-1. Tempeh aroma and texture showed strong correlation between the numbers of bacterial population during the period or stages of tempeh maturation. Moreover, we also found a unique correlation between dynamic of lipolytic population and aroma changes. Free fatty acid profiling indicates that lipolysis activity was presence during fermentation of tempe where each tempeh samples showed some differences in liberation of dominant free fatty acid. 16S rRNA sequencing from a hundred of lipolytic isolates was identified and classified as member of the phylum Proteobacteria, Firmicutes, and Actinobacteria, other isolates were classified as uncultured clone.